2012
DOI: 10.1111/j.1468-3083.2012.04454.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic rate and subcutaneous involvement are prognostic factors for survival after recurrence in patients with only locoregional skin metastasis as the first site of recurrence from cutaneous melanoma

Abstract: The survival after recurrence of melanoma patients that has relapsed with only locoregional cutaneous metastasis depends on the mitotic rate of the primary tumor and the subcutaneous involvement of the metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In Valencia, prospective melanoma cases, seen between January 2004 and July 2013, were all included in the melanoma database of the dermatology department of the Instituto Valenciano de Oncologia ( N = 463). The characteristics of this database have been described in detail elsewhere . For Barcelona, melanoma cases submitted to SLN biopsy were collected from the Melanoma Unit at the Hospital Clinic of Barcelona between October 1996 and 2013 and were recruited from Catalonia as well as further a field as the melanoma clinic at the Hospital Clinic Barcelona is a secondary and tertiary referral center ( N = 678).…”
Section: Methodsmentioning
confidence: 99%
“…In Valencia, prospective melanoma cases, seen between January 2004 and July 2013, were all included in the melanoma database of the dermatology department of the Instituto Valenciano de Oncologia ( N = 463). The characteristics of this database have been described in detail elsewhere . For Barcelona, melanoma cases submitted to SLN biopsy were collected from the Melanoma Unit at the Hospital Clinic of Barcelona between October 1996 and 2013 and were recruited from Catalonia as well as further a field as the melanoma clinic at the Hospital Clinic Barcelona is a secondary and tertiary referral center ( N = 678).…”
Section: Methodsmentioning
confidence: 99%
“…Increasing thickness means ascending rate of recurrence and metastasis. [3][4][5] Special AT-rich sequence binding protein 1 (SATB1) is a nuclear matrix attachment DNA-binding protein, which is predominantly expressed in thymocytes and central nervous system. 6,7 SATB1, generally acknowledged as a genome organizer, tethers multiple genomic loci and recruits chromatin-remodeling enzymes to regulate the chromatin structure and gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…From the Sydney Melanoma Unit, Francken and colleagues commented that the 5‐year survival for in‐transit recurrences (> 3 cm from the original tumour) was 44% ( n = 86) and for distant subcutaneous recurrences the 5‐year survival was only 9% ( n = 27). Messeguer and colleagues recently reported on a subset of 36 patients with locoregional skin metastasis with an estimated 5‐year survival of 52% and found that the mitotic rate of the primary tumour and the subcutaneous involvement of the metastasis influenced survival; factors which were not examined in our series.…”
Section: Discussionmentioning
confidence: 81%
“…Where surgery had not been undertaken at the VMS, a histopathological review to confirm the diagnosis of cutaneous metastases was obtained from VMS pathologists. We grouped what has been called local, satellite, intralymphatic or in‐transit metastases to avoid the varying and arbitrary distinctions between these different entities and to maintain uniformity. It is often difficult to accurately categorise metastases in the region clinically and we therefore chose to group them.…”
Section: Methodsmentioning
confidence: 99%